Study on the Provision of WTO in the Context of Trade and Environmental Issues - Kavyanjali Tewari (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
WTO is the international organization that regulate the trade rules and it’s objective is to make trade smooth and free for nations. WTO was established on 1st January 1995. It was created by Uruguay round negotiation. WTO is located at Geneva Switzerland and it has 166 member those are representing the international trade and it has 604 secretariat staff and a director general. The WTO agreement are signed by the nation who are members and the trading system of WTO was based on GATT . It deals mainly with goods trading but it also covers trading of services, inventions, creations that is intellectual property. WTO can give path to international environmental objectives by providing its rule and agenda. For fulfilling the objective of sustainable development, the natural resources should be used optimally and WTO is always focusing on protecting and conserving the environment. The members of WTO is operating on non discriminatory multilateral trading system. This promote sustainable development together with Environmental Protection. As we know that global trade is the reason for climate changes and pollution. The environment and trade hub provide space to United Nations environmental programmes that work on international trade. The present study focus on the issues that can be handled by WTO. It can reduce cost of living and increase standard of living. WTO can also settle the dispute and reduce the conflict of trade. It can increase growth of economy and generate employment. It can reduce the cost of starting business at international level by reducing the cost and can motivate good governance and help developing countries by providing opportunities for trade. It can also give a strong voice to the weak countries by giving training to the officials of developing country through seminars and various workshops. WTO can increase peace and stability in countries and can support the environment and health. It can be effective without coming on headlines. The present study shows that how WTO can make trade liberal and protect the environment through various provisions.